Cariprazine: A new partial dopamine agonist with a familiar profile. (June 2022) - Hope, Judy; Keks, Nicholas A
Objective: Cariprazine is the third partial dopamine agonist now available in Australia. This paper will review the properties, evidence and likely clinical place of cariprazine. Conclusion: Cariprazine is a partial agonist with high affinity at dopamine D2 and D3 receptors, partial agonism at 5HT1a receptors, moderate 5HT2a and H1 antagonism and no anticholinergic activity. It is rapidly absorbed, is unaffected by food, achieves a peak plasma level in 4–8 hours and has high bioavailability. The half-life of cariprazine and its metabolites is long (7–8 days); steady state occurs in 4–8 weeks. It is hepatically metabolized via 3A4 cytochrome enzymes. Cariprazine is an effective antipsychotic in acute schizophrenia in both short and longer placebo-controlled studies. Cariprazine appears to have small advantages in negative symptoms of schizophrenia. While not approved for bipolar disorder, cariprazine is effective in mania and mixed states but requires doses higher than current maximums recommended. Cariprazine causes more akathisia than aripiprazole or brexpiprazole but is less prone to insomnia, weight gain and sedation. Risks for hyperprolactinaemia and QTc prolongation are low. Cariprazine is another 'metabolically-friendly' antipsychotic for schizophrenia, with advantages for those with negative symptoms, mood symptoms or problems with adherence.